Outcomes and Predictive Factors Associated with Adequacy of Antimicrobial Therapy in Patients with Central Line-Associated Bloodstream Infection - Yokota, Paula Kiyomi Onaga; Marra, Alexandre Rodrigues; Belucci, Talita Rantin; Victor, Elivane da Silva; Santos, Oscar Fernando Pavão dos; Edmond, Michael B. (Frontiers in Public Health, 2016)
Background: Central venous catheters (CVCs) are significant risk factors for bloodstream infection (BSI), which are directly associated with increased morbidity and mortality. Methods: This study was a retrospective cohort study for the time period July 2011 to June 2014, in patients with central line-associated bloodstream infection (CLABSI) to determine the microbiological profile and antimicrobial adequacy of patients with CLABSI in a tertiary hospital. Results: One hundred and twenty one CLABSI cases were identified. 92% (n= 111) of patients had monomicrobial BSI. Gram negative bacteria were the most prevalent (49%, n= 63), with Klebsiella spp predominating (30%, n= 19). Among the Gram-positive bacteria (n= 43, 33%), coagulase-negative staphylococci was the major pathogen (58%, n= 25), and all isolates were methicillin resistant. Antimicrobial therapy was assessed as adequate in 81% (n= 98) of cases. In-hospital mortality was 36% (n=43 cases). Conclusions: Our CLABSI patients had a high mortality, although antimicrobial therapy was appropriate. Gram negative bacteria were responsible for almost half of the cases and there was a high rate of bacteria resistance to extended-spectrum antibiotics.